2017
DOI: 10.1111/pan.13086
|View full text |Cite
|
Sign up to set email alerts
|

Effect of age on the performance of bispectral and entropy indices during sevoflurane pediatric anesthesia: a pharmacometric study

Abstract: Performance of both monitors improves as age increases. Our results suggest a need for the development of new monitor algorithms or calibration to better account for the age-specific EEG dynamics of younger patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 27 publications
1
38
0
Order By: Relevance
“…Last, the profile of the EEG changes observed during xenon anesthesia was found to closely resemble those caused by propofol . Furthermore, although age‐related changes in BIS values in children were observed, it has been suggested that the BIS can be reliably used to monitor depth of anesthesia in children older than 1 year of age, showing better performance with increasing age . We therefore consider the BIS (together with interpretations of clinical signs) a valuable monitor of depth of anesthesia in our patient population.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Last, the profile of the EEG changes observed during xenon anesthesia was found to closely resemble those caused by propofol . Furthermore, although age‐related changes in BIS values in children were observed, it has been suggested that the BIS can be reliably used to monitor depth of anesthesia in children older than 1 year of age, showing better performance with increasing age . We therefore consider the BIS (together with interpretations of clinical signs) a valuable monitor of depth of anesthesia in our patient population.…”
Section: Discussionmentioning
confidence: 74%
“…Fahlenkamp et al 28 showing better performance with increasing age. 31,32 We therefore consider the BIS (together with interpretations of clinical signs) a valuable monitor of depth of anesthesia in our patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, EEG changes observed during xenon anesthesia resembled closely those instigated by propofol [33]. Furthermore, although age-related changes in BIS values in children were observed, it has been suggested that the BIS is a reliable monitor of depth of anesthesia at least in children aged > 1 year, showing better performance with increasing age [34,35]. Note that in our study, the adequacy of depth of anesthesia will primarily be assessed by physiological signs (absence of HR or BP increases and involuntarily movements) and the BIS monitor is only an additional tool to quantify depth of anesthesia.…”
Section: Discussionmentioning
confidence: 93%
“…Jacknife method was used to calculate P k standard errors and hence confidence intervals. As previous published comparable studies including 30‐50 patients showed significant correlation of sevoflurane with the results of processed EEG‐monitoring, we decided to include at least 50 infants and children in this observational study.…”
Section: Methodsmentioning
confidence: 99%